Impact of turning waste on performance and energy balance in thermophilic solid-state anaerobic digestion of agricultural waste. (15th March 2019) - Meng, Lingyu; Xie, Li; Riya, Shohei; Terada, Akihiko; Hosomi, Masaaki
Graphical abstract: Highlights: Solid-state anaerobic digestion was conducted with turning waste in the atmosphere. No significant improvement in methane yield by turning waste during digestion. Mixing every day affected methanogenesis and resulted in acetate accumulation. Mixing every day increased oxidation-reduction potential and CO2 content. No mixing during digestion was recommended based on net energy analysis. Abstract: Mixing is an important operation in solid-state anaerobic digestion (SS-AD) to improve the mass transfer of the solid phase. This study proposed simple turning by loader in common garage-type digester without commonly used mixer or percolation system (simplified SS-AD). In simplified-SS-AD, turning is conducted in open condition. Thus, oxidation of anaerobic sludge during turning would influence digestion performance. Therefore, in this study, the effect of turning wastes by mixing during digestion on a simplified SS-AD fed with rice straw and pig urine was investigated. Four different mixing frequency levels—no mixing (M0) and mixing once a day (M-1/1), once every 3 days (M-1/3) and once a week (M-1/7)—were conducted. Methane yields of M0, M-1/3 and M-1/7 were comparable with each other. Methane yield and lag period of M-1/1 were approximately 61% and 155% of M0 (351.2  mL/g VS and 4.7 days), respectively. Furthermore, the chemical oxygen demand (COD) of acetate accumulated in the digestate of M-1/1 was comparable to the difference in the COD of methane production between M-1/1 and the other treatments. Mixing every day also resulted in a higher oxidation-reduction potential and carbon dioxide content. These findings suggest that methanogenesis was inhibited in M-1/1 by frequent mixing in the atmosphere. Net energy analysis of SS-AD plant operation showed that M0 can obtain the highest net energy gain, whereas net energy production of M-1/7 was reduced by rewarming after mixing. Therefore, no mixing is the most effective approach for the proposed simplified process.